Seasonal and Emission Characteristics of PAHs in the Ambient Air of Industrial Complexes - Yong-koo Lee; Ji-hwan Lee; Nam-gwon Beak; Kyoung-chan Kim; Jin-seok Han (Atmosphere, 2023)
Particulate and gaseous polycyclic aromatic hydrocarbon (PAHs) samples (n = 108) were measured every six days from January to December 2022 at a representative point in the Korean Banwol National Industrial Complex. The measurement results revealed that the concentration of particulate Σ18 PAHs was 7.92 ± 4.04 ng/Sm3 in winter, 1.83 ± 1.99 ng/Sm3 in spring, 1.43 ± 0.95 ng/Sm3 in summer, and 2.58 ± 2.14 ng/Sm3 in autumn. The concentration of gaseous Σ18 PAHs was 3.32 ± 3.72 ng/Sm3 in winter, 6.34 ± 5.95 ng/Sm3 in spring, 8.33 ± 8.13 ng/Sm3 in summer, and 3.88 ± 1.71 ng/Sm3 in autumn. The results of the correlation analysis showed that particulate PAHs have positive relationships with PM10 and PM2.5 and negative relationships with temperature and O3. The diagnostic ratio and PAHs component slope showed that the emission source characteristics of the Banwol National Industrial Complex were dominated by biomass coal combustion over four seasons; however, the influence of petroleum combustion (automobile emissions) was not negligible. As for coal combustion, bituminous coal was the most influential, and lignite was relevant in summer and autumn.